Managing sudden unexpected disruptions in complex projects: the antifragility hierarchy - Usher, Greg; Cantarelli, Chantal C.; Davis, Kate; Pinto, Jeffrey K.; Turner, Neil (Taylor & Francis, 2025)
Projects are prone to a variety of sudden unexpected disruptions across their development cycle, requiring that effective organizations develop strategies for proactively recognizing disruption likelihood and swiftly responding to these events. This paper explores a hierarchy of responses to disruption, based on Taleb’s theory of antifragile system behavior. Following this reasoning, we suggest that when faced with project disruptions, organizations need to investigate the means to trigger a ‘convex’ response that increases value through antifragile thinking. We propose an ‘antifragility hierarchy’ in which three key responses to project disruption are demonstrated, with a range of strategies available for addressing these disruptions. This hierarchy offers a novel conceptualization of responses to project disruption events, suggesting that the options available to organizations range from robust (the least effective) to antifragile (the most constructive). Finally, we offer a set of strategies for effectively responding to disruptions to promote antifragility in projects.
Keywords: 33 Built Environment and Design; 3302 Building; 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; Operations Research; Projects; disruption; resilience; antifragility